Tingkat Kesukaan The Angel Pastry dengan Substitusi Tepung Bonggol Pisang dan Daun Mangga - Yuniastuti, Silvi Dwi; Restiana, Meira; Alfiyanti, Salma; Soesanto, Edy; Maharani, Putri; Aisyah, Siti (Universitas Muhammadiyah Semarang, 2023)
One of the local food ingredients that can be used as a base for making pastry as an alternative diet for obesity in children is banana tubers and mango leaves. Banana stems and mango leaves can be processed into flour which can reduce damage and increase added value. Banana hump flour and mango leaves can be processed into various snacks, one of which is The Angel Pastry. The higher fiber and antioxidant content by substituting banana hump flour and mango leaves in the angel pastryhas the potential to be a filling snack. The aim of this research was to determine the level of preference for The Angel Pastry formulation with the substitution of banana hump flour and mango leaves. The experimental design used in this research was RAL (Completely Randomized Design). The substitution formulation for banana hump flour and mango leaves in making The Angel Pastry is 0,15, and 30%. The resulting Angel Pastry will be tested for the level of liking of 30 semi-trained panelists. The results showed that the substitution of banana hump flour and mango leaves had asignificant effect on the parameters of color, aroma, taste and texture preference level. Substitution of banana hump flour and mango leaves in making The Angel Pastry at 15% is the best treatment with a color preference level value of (4.72); aroma (4.89); taste (4.48); texture (4.82).Keywords: the angel pastry,banana flour, mango leaves, sensory evaluation